Clinical depression and condom use attitudes and beliefs among African American adolescent females. - Brawner, Bridgette M; Davis, Zupenda M; Fannin, Ehriel F; Alexander, Kamila A (The Journal of the Association of Nurses in AIDS Care : JANAC, 2012)
Depression, HIV, and other sexually transmitted diseases (STDs) are growing concerns among African American adolescent females. Theoretical models contribute to identification of mediators of condom use; however, minimal research has addressed the explicit relationship between clinical depression and condom use in African American adolescent females. The authors report results from quantitative surveys with clinically depressed (n = 64) and nondepressed (n = 64) African American adolescent females in two large metropolitan cities in the eastern United States. Theoretical mediators of condom use in the study sample-attitudes, subjective norms, perceived behavioral control, and intentions-were investigated. Significant differences existed between the groups in condom use frequency (U = 356.5, p = .037); however, there were no statistically significant differences in condom use attitudes and beliefs. Although clinically depressed and nondepressed African American adolescent females may hold similar attitudes and beliefs about condom use, differences in condom use frequency may be a psychopathologic occurrence.
Keywords: Adolescent; Adolescent Behavior; Adult; African Americans; Condoms; Depression; Female; Health Knowledge, Attitudes, Practice; Humans; Questionnaires